A Review on Combustion Characteristics of Ammonia as a Carbon-Free Fuel - Jun Li (Frontiers in Energy Research, 2021)
A comprehensive review of combustion characteristics of ammonia (NH3) as a carbon free fuel is presented. NH3 is an attractive alternative fuel candidate to reduce the consumption of fossil fuel and the emission of CO2, soot, and hydrocarbon pollutants, due to its comparable combustion properties, productivities from renewable sources, and storage and transportation by current commercial infrastructure. However, the combustion properties of NH3 are quite different from conventional hydrocarbon fuels, which highlight the specific difficulties during the application of NH3. Therefore, this paper presents comparative experimental and numerical studies of the application of NH3 as a fuel during combustion process, including the combustion properties of laminar burning velocity, flame structures, pollutant emissions for the application of NH3 as a carbon free fuel. This paper presents the burning velocity and pollutant emissions of NH3 alone and mixtures with other fuels to improve the combustion properties. The aim of this paper is to review and describe the suitability of NH3 as a fuel, including the combustion and emission characteristics of NH3 during its combustion process.